2018
DOI: 10.1016/j.flora.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity and aggregation for a widespread mistletoe in Campo Rupestre vegetation

Abstract: Assessment of host infection and distribution patterns are crucial to understand the underling mechanisms that shape parasitic plant spread in natural ecosystems. However, such data remain scarce for mistletoes inhabiting Brazilian campo rupestre vegetation, old-growth montane fire-prone grasslands. We evaluated the host range and distribution patterns of the mistletoe Psittacanthus robustus (Loranthaceae) at seven 1-ha plots located at in Serra do Cipó, southeastern Brazil. We investigate if the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
(72 reference statements)
0
11
1
Order By: Relevance
“…Classical studies about parasitism in plants indicate that parasitic species rarely infect just one host species (Kuijt 1969;Norton & Lange 1999). Despite other studies indicating that the existence of a preferential host is common, other species are often complementarily parasitized (Marvier & Smith 1997;Guerra et al 2018). In our study, we observed that the preference by hosts at species level was sharply different between fragments.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Classical studies about parasitism in plants indicate that parasitic species rarely infect just one host species (Kuijt 1969;Norton & Lange 1999). Despite other studies indicating that the existence of a preferential host is common, other species are often complementarily parasitized (Marvier & Smith 1997;Guerra et al 2018). In our study, we observed that the preference by hosts at species level was sharply different between fragments.…”
Section: Discussioncontrasting
confidence: 69%
“…There is a wide variety in host specificity among parasitic plants at species or genus level (Kuijt 1969;Norton & Lange 1999;Su et al 2012;Guerra et al 2018), and this diversity is essential to understanding historical and ecological aspects that determine the associations between parasite and host (Stireman & Singer 2003). Some studies suggest the existence of functional patterns of parasitism (Ward 1992;Arruda et al 2006) and evolutionary adaptations that increase the reliance of the parasite on the host (Schneeweiss 2007;Conn et al 2015;Těšitel 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its buzz-pollinated flowers with poricidal anthers, heterostemony, and pollen as the only reward are dependent on interbreeding; the large, crepuscular bees promote outcrossing within and among patches of naturally-isolated populations on rocky outcrops. Guerra et al (2018) explore the host range and distribution patterns of the mistletoe Psittacanthus robustus (Loranthaceae). Four species of trees (all within Myrtales) comprised 95% of infested individuals, with prevalence increasing with host height for all species and a highly-aggregated distribution in few taller host trees.…”
Section: The Ecology Of Species Interactionmentioning
confidence: 99%
“…We selected bee‐pollinated Fabaceae species (Dafni and O’Toole, 1994; Potts et al, 2005; Gottsberger and Silberbauer‐Gottsberger, 2006; Guerra et al, 2018) of three seasonally dry vegetation types: the tropical campo rupestre and cerrado and a temperate Mediterranean shrubland (Appendix S1). The studied species were identified by specialized bibliography, herbarium collections, or based on previous studies developed at the same study sites (Blanca et al, 2009; Rocha et al, 2016; Camargo et al, 2019; Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…Fabaceae is an important family with high species diversity (770 genera and 19500 species) and a cosmopolitan distribution in a huge variety of habitats (Koenen et al, 2013; Lewis et al, 2013; Azani et al, 2017). Most Fabaceae species rely on bee as pollinators (Potts et al, 2005; Gottsberger and Silberbauer‐Gottsberger, 2006; Guerra et al, 2018); thus, differences in the evolution of specific color signals to attract bees across different environmental conditions are expected.…”
mentioning
confidence: 99%